A novel murine model of pyoderma gangrenosum reveals that inflammatory skin-gut crosstalk is mediated by IL-1β-primed neutrophils - Jatana, Samreen; Ponti, András K.; Johnson, Erin E.; Rebert, Nancy A.; Smith, Jordyn L.; Fulmer, Clifton G.; Maytin, Edward V.; Achkar, Jean-Paul; Fernandez, Anthony P.; McDonald, Christine (Frontiers in Immunology, 2023)
Pyoderma gangrenosum (PG) is a debilitating skin condition often accompanied by inflammatory bowel disease (IBD). Strikingly, ~40% of patients that present with PG have underlying IBD, suggesting shared but unknown pathogenesis mechanisms. Impeding the development of effective treatments for PG is the absence of an animal model that exhibits features of both skin and gut manifestations. This study describes the development of the first experimental drug-induced mouse model of PG with concomitant intestinal inflammation. Topical application of pyrimidine synthesis inhibitors on wounded mouse skin generates skin ulcers enriched in neutrophil extracellular traps (NETs) as well as pro-inflammatory cellular and soluble mediators mimicking human PG. The mice also develop spontaneous intestinal inflammation demonstrated by histologic damage. Further investigations revealed increased circulating low-density IL-1β primed neutrophils that undergo enhanced NETosis at inflamed tissue sites supported by increase in circulatory citrullinated histone 3, a marker of aberrant NET formation. Granulocyte depletion dampens the intestinal inflammation in this model, further supporting the notion that granulocytes contribute to the skin-gut crosstalk in PG mice. We anticipate that this novel murine PG model will enable researchers to probe common disease mechanisms and identify more effective targets for treatment for PG patients with IBD.